Edukacja niepubliczna wobec wyzwań reformy edukacji - Pierzchała, Jacek (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
The paper entitled 'Non-public education in the face of challenges presented by the education reform' is an attempt to show the issues of the third sector in the context of the projected education reform. In the first part of the thesis the legal framework of non-public education in Poland is presented. Moreover, the extent of the problem is shown by analysing the obtained statistical data. The second part of the work is focused on the analysis of the legislative changes and the arising obligations for private educational entities. Also, the challenges for the third sector are indicated. The conclusions are presented in the summary of the thesis.
Keywords: public tasks; administration; school; non-public education; reform